Evolution of the physical properties of soils containing microplastics under high stress conditions - Lei Xue; Xiaoran Li; Qiang Sun; Yimeng Zhou; Jingjing Nan (Case Studies in Thermal Engineering)
Microplastics (MPs) in soil significantly impact human health and ecosystems, making it critical to understand their physical properties. These properties can also be altered by varying depths of geostress. In this study, loess samples with plastic contents of 0 %, 0.5 %, 1 %, and 1.5 % were subjected to pressure using a material testing system under different stress conditions. The resistivity and wave velocity of the plastic loess were measured. The results revealed that wave velocity decreased gradually with increasing plastic content. Additionally, both resistivity and wave velocity increased with rising stress levels. Notably, resistivity initially decreased and then increased as plastic content rose, with the minimum resistivity occurring at approximately 1 % plastic content. The presence of MPs was also found to affect the formation of soil aggregates. These findings provide a theoretical basis and reference for better understanding the physical properties of plastic-containing deep loess and for nondestructively monitoring plastic content in loess through physical exploration methods.